1996
DOI: 10.1088/0953-4075/29/22/010
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of 4d-electrons in singly charged Xe ions

Abstract: Using a photon-ion merged-beam technique, we measured the relative yield spectra of Xe 2+ and Xe 3+ ions created by photoionization of Xe + ions as a function of the photon energy in the 4d ionization region. The Xe 3+ ion production, i.e. the double-electron ionization process is found to be dominant throughout the energy range investigated. A broad structure of 4d excitation ionization around 100 eV photon energy was observed in the Xe 3+ yield spectrum. A spectral shoulder was observed for Xe 3+ at around 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 24 publications
5
38
0
Order By: Relevance
“…The giant resonance process involved in the TS processes must be largely dominated by forward scattering under the experimental conditions where energies of all the incident and outgoing electrons are very high compared with the energy loss. In addiiton, photoion yield measurements 158 have shown that the giant resonance profile of Xe + is similar in both shape and energy to that of Xe. Hence one can take the peak energy of the EELS spectrum in Figure 17b as a representative of E gr , i.e., E gr = 100 eV.…”
mentioning
confidence: 96%
“…The giant resonance process involved in the TS processes must be largely dominated by forward scattering under the experimental conditions where energies of all the incident and outgoing electrons are very high compared with the energy loss. In addiiton, photoion yield measurements 158 have shown that the giant resonance profile of Xe + is similar in both shape and energy to that of Xe. Hence one can take the peak energy of the EELS spectrum in Figure 17b as a representative of E gr , i.e., E gr = 100 eV.…”
mentioning
confidence: 96%
“…Results on the ion spectra of Xe 1 using synchrotron radiation in the spectral range of the 4d excitation have been presented already by Sano et al [7]. O'Sullivan et al [8] investigated the 4d excitation along the isonuclear series I, I 1 , and I 21 by photoabsorption in a laser-produced plasma.…”
mentioning
confidence: 96%
“…It represents the variation of the sum of the intensity of the three main isotopic components (m 129, 131, and 132 u) of Xe 2 ions as a function of the photon energy. All previous experiments on Xe ions, realized using merged-beam setups [18][19][20][21], as well as the previous theoretical investigations [21,22] have focused on the higher energy region of 4d excitations, which is out of the range considered here. The tabulated positions of the different thresholds for the various terms of the Xe 2 5p 4 configuration [17] are reported as vertical bars.…”
mentioning
confidence: 99%